Analyzing Critical Thinking Skills of Physics Preservice Teachers on Electricity and Magnetism - M. Furqon; Parlindungan Sinaga; Liliasari; Lala Septem Riza (Jurnal Penelitian Pendidikan IPA, 2023)
The primary objective of education is to equip students with the necessary skills and knowledge to effectively engage in their chosen professions and make meaningful contributions to their respective communities. One of the skills needed is critical thinking skills. The mastery of critical thinking skills is deemed essential for preservice physics teachers in the 21st century. This study aims to analyze the critical thinking skills of preservice physics teacher on electricity and magnetism. The research involved 38 preservice physics teacher students at one of the LPTK’s in Indonesia. The research method applied is descriptive quantitative. The research instrument used was a description test, namely the Critical Thinking Skills in Electricity and Magnetism (CTEM). Test yang didiadopsi dari Tiruneh et al. (2017). The results showed that the critical thinking skills of physics teacher candidates were low. Efforts are needed to improve critical thinking skills through methods, models, media, and other interventions in learning.